2007
DOI: 10.1007/s12262-007-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Her-2/neu protein over expression in Indian breast cancer patients

Abstract: Background Racial disparity in presentation and outcome of breast cancer is established but cause is unexplained . Many studies show various molecular markers for racial differences in the prognosis of breast cancer. There is scarcity of data on prognostic signifi cance of HER-2/neu in Indian breast cancer. Aims and ObjectiveTo know incidence and prognostic signifi cance of HER-2/neu expression in Indian patients.To correlate HER-2/neu Expression with other prognostic markers and ER/PR Receptor status. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
9
22
1
Order By: Relevance
“…Further, Saleh and Abdeen [23] reported increased positivity of ER with age while PR positivity did not have any significant variation. A previous Western study also showed similar results, though other studies showed no correlation between age and Her2/neu expression [14,24]. Tumor size in our study was 2 cm and 54.9 % of cases have T2 tumors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Further, Saleh and Abdeen [23] reported increased positivity of ER with age while PR positivity did not have any significant variation. A previous Western study also showed similar results, though other studies showed no correlation between age and Her2/neu expression [14,24]. Tumor size in our study was 2 cm and 54.9 % of cases have T2 tumors.…”
Section: Discussionsupporting
confidence: 85%
“…This ER and PR expression is lower and Her2/neu expression is higher when compared with the Western studies which have shown 73 % ER positivity and 58 % PR positivity and 17-30 % Her2/neu positivity [12]. The frequency of Her2/ neu positivity varies among Indian studies such as 43.2 % in Vaidyanathan et al [13] study, 40.2 % in Munjal et al [11] study and 46.3 % in Kumar et al [14] study. This variation in Her2/neu positivity may be due to method of detection of Her2/neu in those studies.…”
Section: Discussionmentioning
confidence: 95%
“…Kumar et al from India also found similar results 13 . They reported mean tumor size 3.4 cm and 85.8% of their cases were having tumor size more than 2 cm.…”
Section: Molecular Subtypes Immunohistochemical Characterizationsupporting
confidence: 56%
“…Vaidyanathan et al from the same region reported it to be 43.2% positivity in BC cases (Vaidyanathan et al, 2010). This finding was further supported by a group from Indore city Central India which showed 40.2% positivity and Varanasi city from Northern India exhibited 46.3% positivity (Kumar et al, 2007;Munjal et al, 2009). Reports from Asian , 2006;Naeem et al, 2008;Kamil et al, 2010).…”
Section: Discussionmentioning
confidence: 64%